A Ten Year Retrospective Follow-Up Of Drug Dependence Career. - Navaratnam, V.; Foong, K.; Hoo, S.K.; Wong, P.C. (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1990)
This research report presents findings on addiction careers over a ten year period. One of the objectives of this study is to describe the patterns of drug use, criminality, arrest, incarceration and legitimate employment which characterised the addicts, and to relate these configurations to characteristics prior to addiction, during the periods of abstinence and at the point of interview.